Intestinal barrier damage contributes to a higher prevalence of frailty in aging people living with HIV: a retrospective case control study in a Chinese cohort - Xu, Xiaolei; Ouyang, Jing; Yan, Jiangyu; Lu, Yanqiu; Harypursat, Vijay; Wu, Hao; Chen, Yaokai (Frontiers in Immunology, 2024)
Abstract Background: It has been previously demonstrated that intestinal barrier damage is one of the underlying mechanisms leading to frailty in non-HIV-infected aging populations. However, there is a paucity of direct evidence which demonstrates the association between intestinal barrier damage and frailty in people living with HIV (PLWH). Methods: The present study is a retrospective case control study. Participants older than 50 years old were stratified into a frail/pre-frail group (case group) and non-frail group (control group) according to the Fried frailty phenotype. We collected and curated data concerning socio-demographic variables, psychological states and social functioning, and clinical information associated with the identification of biomarkers of intestinal barrier damage, microbial translocation, and levels of inflammatory cytokines of participants. Results: The case group had significantly higher levels of Reg-3α (p=0.042) and I-FABP (p=0.045) compared to the control group. We further observed, after adjusting for confounding factors by logistic regression analysis, that I-FABP levels remained significantly higher in the case group compared to the control group (p=0.033). Also, Fried Phenotype scores positively correlated with I-FABP levels (rs=0.21, p=0.01), LPS levels (rs=0.20, p=0.02), and sCD14 levels (rs=0.18, p=0.04). Moreover, the study confirmed both the positive correlation between inflammatory cytokines (IL-6 and IP-10) with frailty in aging PLWH, and between inflammatory cytokines (IL-6, IL-8 and IP-10) with biomarkers of intestinal barrier dysfunction in older PLWH. Conclusion: The present study indicates that the inflammation induced by intestinal barrier damage/dysfunction is likely to contribute to frailty in aging PLWH.